2017
DOI: 10.1590/0037-8682-0478-2016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the bla OXA , bla VEB-1 , and bla GES-1 genes and resistance patterns of ESBL-producing Pseudomonas aeruginosa isolated from hospitals in Tehran and Qazvin, Iran

Abstract: Introduction:Pseudomonas aeruginosa is one of the most common nosocomial pathogens. The emergence of extended spectrum β-lactamases (ESBLs) has been increasingly reported as a major clinical concern worldwide. The main aim of the present study was to determine the distribution of bla OXA , bla PER-1, bla VEB-1, and bla GES-1 genes among ESBL-producing P. aeruginosa isolated from two distinct provinces in Iran. Methods: In this study, a total of 75 (27.5%) ESBL-producing isolates were identified from 273 P. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
2
21
1
Order By: Relevance
“…In a study in Thailand, from 118 nonduplicate clinical isolates of P. aeruginosa, 6.7% carried the bla VEB-1, bla PER-1 and bla TEM-1 (and derivatives) genes, and bla SHV-1 was not observed (21). The notably high prevalence of bla PER-1 , bla VEB-1 , bla TEM and bla SHV observed in this study indicates the wide-spread dissemination of ESBL-encoding β-lactamase genes in Iran, which is in accordance with previous reports (22,25,33 (25). In another study in Tehran (Iran), 21.6% of P. aeruginosa isolates carried the bla PER-1 gene (33).…”
Section: / Enayatzadeh and Colleaguessupporting
confidence: 90%
See 1 more Smart Citation
“…In a study in Thailand, from 118 nonduplicate clinical isolates of P. aeruginosa, 6.7% carried the bla VEB-1, bla PER-1 and bla TEM-1 (and derivatives) genes, and bla SHV-1 was not observed (21). The notably high prevalence of bla PER-1 , bla VEB-1 , bla TEM and bla SHV observed in this study indicates the wide-spread dissemination of ESBL-encoding β-lactamase genes in Iran, which is in accordance with previous reports (22,25,33 (25). In another study in Tehran (Iran), 21.6% of P. aeruginosa isolates carried the bla PER-1 gene (33).…”
Section: / Enayatzadeh and Colleaguessupporting
confidence: 90%
“…In a study in Thailand, the rate of resistance to ceftazidime, cefepime, amikacin, gentamicin, ciprofloxacin, levofloxacin, imipenem, meropenem and ciprofloxacin was 44.91%, 28.81%, 18.64%, 25.42%, 43%, 49.15%, 31.36%, 33% and 48.3%, respectively (21). In Iran, most studies have reported high resistance rates to amikacin and aztreonam and low resistance rate to levofloxacin and polymexin B (22,23), which might indicate the imprudent use of amikacin and aztreonam in Iran. In the present study, 95% of the P. aeruginosa isolates were MDR, which is similar to the results of studies performed by Safaei et al (24) and Mirsalehian et al (25).…”
Section: Discussionmentioning
confidence: 99%
“…The β-lactamase bla VEB-9 (19, 25.33%), formerly known as bla VEB-1a , was the most frequent ESBL gene identified in the present study [ 11 ]. bla VEB-1 is one of the most frequently reported ESBLs in P. aeruginosa from the Middle East including Kuwait, Saudi Arabia and Iran [ 13 15 ]. Though bla VEB-9 was reported from Thailand and Eastern Europe, to the best of our knowledge, it has not been previously reported from the Middle East [ 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial treatment is further hampered by the production of extended spectrum beta-lactamases and metallo beta-lactamases [20,47]. As at now, ESBLs in P. aeruginosa are described globally with MBLs also being reported on a growing basis in recent years [15,22].…”
Section: Discussionmentioning
confidence: 99%